Research design in social work qualitative, quantitative & mixed methods - Campbell, Anne; McGlade, Anne; Taylor, Brian J. (Professor of social work) (Transforming Social Work Practice Series, 2017)
Social work research often focuses on qualitative designs and many students believe that the quantitative research pathway is either too complicated or is beyond their grasp. This book outlines how social work students can undertake a research project from either a qualitative, quantitative or mixed methodological approach. The authors introduce key concepts in an accessible and structured manner and go on to demonstrate each of the approaches from inception of research idea, to realization of methodological approach, to research process, to data analysis and conclusion